Issues in the Development of Location-Based Games. (22nd February 2011) - Jacob, João Tiago Pinheiro Neto; Coelho, António Fernando
Abstract : As new and more powerful mobile devices arrive, such as smartphones, tablets and PDAs, so do new ways of interaction emerge for the users and developers to explore. These devices allow for the creation of never-before-seen applications, using the broad range of inputs and sensors these devices integrate (such as accelerometers, light sensors, electronic compasses, GPS sensor among others), that allow for more ubiquous and personalized experiences. This paper explores issues that arise during the development and design phases of such games, as well as posible solutions for them. Finally we present, a framework for the development of location-based games that is sensible to these issues. This framework was created and tested thanks to a proof-of-concept location-based game (Geo-Wars).